Online distribution system state estimation via stochastic gradient algorithm - Huang, Jianqiao; Zhou, Xinyang; Cui, Bai (Electric power systems research, 2022)
Distribution network operation is becoming more challenging because of the growing integration of intermittent and volatile distributed energy resources (DERs). This motivates the development of new distribution system state estimation (DSSE) paradigms that can operate at fast timescale based on real-time data stream of asynchronous measurements enabled by modern information and communications technology. To solve the real-time DSSE with asynchronous measurements effectively and accurately, this paper formulates a weighted least squares DSSE problem and proposes an online stochastic gradient algorithm to solve it. The performance of the proposed scheme is analytically guaranteed and is numerically corroborated with realistic data on IEEE 123-bus feeder. •Power-injection-based distribution system state estimation.•Online state estimation with stochastic gradient algorithm.•Highly efficient and accurate algorithm.•Online simulation of 1-second granularity with real data.